Edukasi dan Pelatihan Pembuatan Sabun Cair Berbasis Minyak Jelantah bagi Siswa SMK Semesta Bumiayu Brebes - Aldi Budi Riyanta; Rizki Febriyanti; Hanif Nur Assyifa; Mella Melliyana; Fathulia Rizqina; Mohammad Farhan Aziz (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this devotion gives students the skills to make soap from jelantah oil. The method is done with oration combined with direct practice to students. Activity assessments are measured from pretest and postest values performed during activities. The results of the devotion that has been done able to improve the skills of students in formulating soap from jelantah oil reached 48.47% of the assessment results given.